2010
DOI: 10.1007/s11738-010-0527-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural antioxidants of plant origin against ozone damage of sensitive crops

Abstract: The increasing concentrations of ambient ozone observed during recent decades in many industrial and rural regions of the world present hazard for vegetation and human health. The problem of protection of sensitive vegetation from ozone damage could be ameliorated by replacement of sensitive biotypes with more tolerant ones as well as by application of chemical protectants. However, application of synthetic protectants will pollute the environment and agricultural production and may also have dose-dependent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 67 publications
(95 reference statements)
2
18
0
Order By: Relevance
“…The results shows that exogenous antioxidants application to wheat plants, inhibited growth of Bipolaris on them and enhanced synthesis of PR protein and chitinase. Our findings are in line with Didyk and Blum (2011), reported exogenous application of antioxidants limits foliar necrosis, biomass reduction and alteration of metabolism caused by O 3 stress. Querictin and tagetes leaf extract reduced foliar injury by 10-13% and 14%, respectively, in Trifolium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results shows that exogenous antioxidants application to wheat plants, inhibited growth of Bipolaris on them and enhanced synthesis of PR protein and chitinase. Our findings are in line with Didyk and Blum (2011), reported exogenous application of antioxidants limits foliar necrosis, biomass reduction and alteration of metabolism caused by O 3 stress. Querictin and tagetes leaf extract reduced foliar injury by 10-13% and 14%, respectively, in Trifolium.…”
Section: Discussionsupporting
confidence: 93%
“…Querictin and tagetes leaf extract reduced foliar injury by 10-13% and 14%, respectively, in Trifolium. subterraneum exposed to ambient O 3 level for 28 days (Didyk and Blum 2011). Ascorbic acid application reduced the visible leaf injury by 50-89% and 100% in 45-55 ppb and 0-250 ppb O 3 exposed Nicotiana tabaccum (Chen and Gallie 2005).…”
Section: Discussionmentioning
confidence: 97%
“…The damage caused to plants as a consequence of high O 3 concentrations could be mitigated or prevented by application of antioxidants, such as ascorbic acid, glutathione, and the antiozonant ethylenediurea (EDU) (Didyk and Blum, 2010;Feng et al, 2010;Lisko et al, 2014;Manning, 2000;Manning et al, 2011;Paoletti et al, 2009;Saitanis et al, 2015). These antioxidants and EDU have been extensively used in USA and many European countries to protect crop yield loss from ambient ozone.…”
Section: Applying Chemical Protective Agents At Key Phenological Stagesmentioning
confidence: 99%
“…It has been found that ozone treatment induces synthesis of flavonoids by enhancing activities of flavonoid pathway enzymes and phenylpropanoids accumulation [4,[10][11][12][13]. Elevated O 3 increased the contents of flavonoids in the leaves of birch [12,14] and maize [15].…”
Section: Introductionmentioning
confidence: 99%